Query Optimization Methods and Techniques on Production Database Server - Singh, Tarandeep; Sood, Sanjay Prakash; Bhatti , Harbax Singh (Gyan Management Journal, 2018)
We put forward a come close toward for query optimization on production server database by reducing weight and load, as an important skill for developers and database administrators (DBAs). In order to optimize the query and get the considered necessary outputs within time limits developer and DBA must understand the query optimization techniques. In today's working, query optimization provides level-headed approach for extracting reports for pronouncement making for any organization. In the very foundation of the project when there is not much data in database the reports are unproblematic to fetch. When the data starts ever-increasing and we need reports for long episode of time within time limit then we may have to optimize the existing queries.
Keywords: TKPROF; RBO; CBO; INDEX; TRACE SQL